Militarism, conflicts and indiscipline in police practices in the State of São Paulo during the First Brazilian Republic - Francisco de Souza, Luis Antonio [UNESP] (Univ do Vale do Rio Dos Sinos, 2012)
This article examines the challenges involved in the process of police militarization and implementation of police discipline in the State of São Paulo during the First Brazilian Republic (1889 to 1930). The implementation of a militarized police model, initiated by the 1906 French Military Mission, was not fully able to deal with indiscipline issues among policemen. Beyond creating problems of its own, such as fostering a corporatist culture and strengthening rigid hierarchies, military discipline prevented police forces to address new issues that would affect its practices. Documents in the São Paulo State Public Archive provides a window to the daily violence, the personal compromises, the institutional conflicts and the political meddling that was part of police life in the State of São Paulo at the turn of the century.
Keywords: police; police history; militarism; indiscipline; São Paulo; First Brazilian Republic